2022
DOI: 10.1161/strokeaha.121.036050
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Large Animal Models for Acute Ischemic Stroke: Which Model to Use?

Abstract: Translation of acute ischemic stroke research to the clinical setting remains limited over the last few decades with only one drug, recombinant tissue-type plasminogen activator, successfully completing the path from experimental study to clinical practice. To improve the selection of experimental treatments before testing in clinical studies, the use of large gyrencephalic animal models of acute ischemic stroke has been recommended. Currently, these models include, among others, dogs, swine, sheep, and nonhum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 106 publications
(98 reference statements)
3
34
0
2
Order By: Relevance
“…Large animal stroke models could aid in the selection of the most viable therapies to test in clinical trials . 126 A recent study in swine subjected to stroke via an endovascular approach showed that while gadolinium enhancement on T1-weighted MRIs was marginal at 24 hours, likely the result of restricted access of the contrast agent due to limited perfusion of the ischemic territory, immunoglobulin extravasation into the ischemic territory was elevated both subacutely (24 hours) and chronically (up to 3 months), 127 which is similar to findings from clinical studies showing persisting BBB dysfunction in ischemic stroke. 128,129 Despite the mostly neutral or negative outcomes of clinical trials, there are some positive preliminary findings in ischemic and hemorrhagic stroke for anti-inflammatory treatments, such as with lymphocyte-trapping agent fingolimod, [130][131][132] approved to treat relapsing forms of multiple sclerosis.…”
Section: Translation To Humans and Concluding Remarksmentioning
confidence: 58%
See 1 more Smart Citation
“…Large animal stroke models could aid in the selection of the most viable therapies to test in clinical trials . 126 A recent study in swine subjected to stroke via an endovascular approach showed that while gadolinium enhancement on T1-weighted MRIs was marginal at 24 hours, likely the result of restricted access of the contrast agent due to limited perfusion of the ischemic territory, immunoglobulin extravasation into the ischemic territory was elevated both subacutely (24 hours) and chronically (up to 3 months), 127 which is similar to findings from clinical studies showing persisting BBB dysfunction in ischemic stroke. 128,129 Despite the mostly neutral or negative outcomes of clinical trials, there are some positive preliminary findings in ischemic and hemorrhagic stroke for anti-inflammatory treatments, such as with lymphocyte-trapping agent fingolimod, [130][131][132] approved to treat relapsing forms of multiple sclerosis.…”
Section: Translation To Humans and Concluding Remarksmentioning
confidence: 58%
“…The use of large gyrencephalic animal models, including sheep, dogs, swine, and nonhuman primates, has been recommended by the Stroke Therapy Academic Industry Roundtable to complement the preclinical testing in rodents and enhance the clinical translation of promising cerebroprotective strategies. Large animal stroke models could aid in the selection of the most viable therapies to test in clinical trials 126 . A recent study in swine subjected to stroke via an endovascular approach showed that while gadolinium enhancement on T1-weighted MRIs was marginal at 24 hours, likely the result of restricted access of the contrast agent due to limited perfusion of the ischemic territory, immunoglobulin extravasation into the ischemic territory was elevated both subacutely (24 hours) and chronically (up to 3 months), 127 which is similar to findings from clinical studies showing persisting BBB dysfunction in ischemic stroke.…”
Section: Translation To Humans and Concluding Remarksmentioning
confidence: 99%
“…Rodent ischemic CVA DWI abnormalities resolve faster than those observed in humans ( 4 , 9 , 31 , 50 ). Dogs and primates are more gyrencephalic, have more gray matter volume, and have a larger proportion of subcortical white matter affected by induced stroke, as compared to rodents ( 50 ). Consistent with previous reports, we show examples of presumed canine CVAs with reduced ADC values up to 5 days after the onset of signs.…”
Section: Discussionmentioning
confidence: 82%
“…On the other hand, animal models offer a valuable tool, but the animal brain physiology has critical differences compared to the human brain. Additionally, animal models are difficult to monitor on a cellular level and are associated with severe side effects, or even death, posing serious ethical concerns [ 18 ].…”
Section: Introductionmentioning
confidence: 99%